Die thomistische Scholastik und die husserlische Phänomenologie in der Gedankenwelt von Edith Stein - Kormos, József (Verbum – Analecta Neolatina, 2004)
Edith Stein (1891-1942) was at first a student of Edmund Husserl in Göttingen, later she became his assistant in Freiburg. According to Husserl, she had a thorough knowledge of phenomenology, and she applied it as well. Having become a Catholic and translating De veritate by St. Thomas Aquinas, she turned to the method of Aquinas with new interest. As a consequence, she integrates the topic of faith in the Husserlian phenomenology. She assumes faith as an epistemological source. This faith postulates its subject matter, i.e., the existence of God, because of intentionality. This way, she claims to avoid the danger if subjectivism or solipism present in the Husserlian brackets. Her interpretation of faith is twofold as well as the essence revealed in the case of Husserl. For Stein, the faith found in the transcendental sphere is also valid knowledge in everyday reality, although this knowledge by faith - and here she relates to the mystics - is also different from ordinary knowledge inasmuch as it refers to the essence, God, and the existence of God at the same time. Using the Husserlian phenomenology and the scholastics of Aquinas, Stein aims at a religious philosophical grounding in which the existence-postulate of Aquinas and the essence-postulate of Husserl are both present.